Punitive Damage Effects on Post-Loss Bargaining and Settlement - Eckles, David L. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2010)
We examine the theoretical effects of punitive damages and how they affect pretrial bargaining of insurers and insureds. We also seek to determine how the introduction of symmetric punitive damage awards could affect the bargaining, and by extension, the entire litigation process. We find that asymmetric punitive damage awards do tend to increase the bargaining power of insureds and by allowing for a symmetric system the bargaining power of insureds and insurers are more balanced. We also find that altering the mechanisms for court cost payments also can alter the probability of out of court settlements.